ANALISIS BENTUK DAN TRUKTUR NYANYIAN ODE TO JOY KARYA LUDWIG VAN BEETHOVEN - Philby Tafuakan (Tambur : Journal of Music Creation, Study and Performance, 2021)
Based on the results of the research conducted, it can be concluded that this study aims to determine the shape and musical structure of the Ode To Joy song. Song of Ode To Joy (English Version) or in its original title An die Freude is part of Symphony No. 9 in D Minor, Opus 125 which is the last symphony work of Ludwig Van Beethoven. The songs in this symphony basically give a meaning about freedom, brotherhood, joy, brotherhood among human beings and an expression of gratitude to God. Overall, Symphony No. 9 in D Minor, Opus 125 begins its long introduction with a d minor progression and ends with a D major chord progression. We know that chord progressions also represent the expression of the composer's feelings. The minor chord generally expresses feelings of sadness or suggests sad and dark conditions, while the major chord expresses feelings of happiness and joy as well. The composer also expressed the meaning of freedom through dynamic play, change of interest, and chord progression. Symphony No. 9 in D Minor, Opus 125 has four moves by making Chord D a tonality. The introductory part of the fourth movement is basically a repetition of the I-III movement which symbolizes brotherhood and unity. The songs in this symphony also have three major themes in the exposition, development and recapitulation of this Symphony as a whole consisting of 937 bars.